Dampak Over Kapasitas Di Lembaga Pemasyarakatan Kelas I Cipinang Bagi Narapidana - Utomo Bimantoro; Muhammad Nurul Irfan; Mara Sutan Rambe (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The overcapacity of convicts resulted in the adoption of negative living procedures at Cipinang Class I Prison, which has the ability to impede the reintegration efforts of inmates, who are feared to be able to thwart the prison's original purpose. This thesis seeks to understand the preventive and resolution efforts against the repetition of crimes in Cipinang Class I Prison as a result of the prison's overcrowding by determining in advance the impact of the prison's overcrowding on inmates' rights. This study employs a type of empirical juridical research by conducting field interviews with the Class I Cipinang Prison, followed by studies on literary materials by reading, examining, and analyzing literature to generate studies linked to the theme of this thesis. The results indicated that the overpopulation of Cipinang Class I Prison led to a lack of supervision of detainees, which disrupted the rights of inmates. In prisons when the number of inmates exceeds the capacity, the function and purpose of prisons are impeded, and jails may become criminal academies. To prevent this from occurring, Cipinang Class I Prison conducts preventative measures consisting of unannounced searches of inmate dormitories and interactions with convicts. In addition, as a kind of countermeasures, Cipinang Class I Prison administers sanctions based on the category broken by convicts.